Keberlangsungan Tradisi Jawa Dalam Pernikahan Di Tanah Melayu (Studi Kasus Di Kecamatan Kunto Darussalam Provinsi Riau) - Badi’, Ahmad; Candra, Dian Galuh Ayu (Sosaintek: Jurnal Ilmu Sosial Sains dan Teknologi, 2024)
The focus of this research discusses how the challenges faced by the community and how the strategy carried out by the community of Kunto Darussalam Subdistrict. This research aims to find out the challenges and to describe the strategies carried out by the people of Kunto Darussalam Subdistrict in maintaining and preserving the Javanese wedding culture in Kunto Darussalam Subdistrict itself. The research method used is a qualitative method with this method researchers are much easier in producing descriptive data, namely trying to understand and understand an event and problems that occur, where research data is taken from notes, books, journals, interviews and other literacy. Research on the existence of Javanese Tradition in marriage in Malay land in Kunto Darussalam District has been conducted. This research has found five challenges faced by the community of Kunto Darussalam Sub-district in preserving the Javanese wedding tradition: 1). There is no institution that oversees. 2). Differences between cultural guides. 3). Low Economy. 4). Cultural acculturation. 5). Lack of Love for Culture. This research has also found five strategies carried out by the community of Kunto Darussalam Subdistrict in striving for the existence of Javanese traditional marriage culture, consisting of: 1). Promoting Blokeran culture. 2). Qualified traditional practitioners. 3). Promoting Rewang culture 4). Determining the good date. 5). Promoting the Sinoman culture.